Cancer stem cell regulated phenotypic plasticity protects metastasized cancer cells from ferroptosis - Wu, Mingming; Zhang, Xiao; Zhang, Weijie; Chiou, Yi Shiou; Qian, Wenchang; Liu, Xiangtian; Zhang, Min; Yan, Hong; Li, Shilan; Li, Tao; Han, Xinghua; Qian, Pengxu; et al. (Nature communications, 2022)
Cancer cells display phenotypic equilibrium between the stem-like and differentiated states during neoplastic homeostasis. The functional and mechanistic implications of this subpopulation plasticity remain largely unknown. Herein, it is demonstrated that the breast cancer stem cell (BCSC) secretome autonomously compresses the stem cell population. Co-implantation with BCSCs decreases the tumor-initiating capacity yet increases metastasis of accompanying cancer cells, wherein DKK1 is identified as a pivotal factor secreted by BCSCs for such functions. DKK1-promotes differentiation is indispensable for disseminated tumor cell metastatic outgrowth. In contrast, DKK1 inhibitors substantially relieve the metastatic burden by restraining metastatic cells in the dormant state. DKK1 increases the expression of SLC7A11 to protect metastasizing cancer cells from lipid peroxidation and ferroptosis. Combined treatment with a ferroptosis inducer and a DKK1 inhibitor exhibits synergistic effects in diminishing metastasis. Hence, this study deciphers the contribution of CSC-regulated phenotypic plasticity in metastatic colonization and provides therapeutic approaches to limit metastatic outgrowth. The contribution of breast cancer stem cells (BCSCs) to metastasis needs further elucidation. Here, the authors show that BCSCs secrete DKK1 to protect metastasizing cancer cells from ferroptosis via upregulation of SLC7A11, and further show that the combination of a ferroptosis inducer with a DKK1 inhibitor reduces metastasis.